2018
DOI: 10.4314/ijbcs.v12i2.12
|View full text |Cite
|
Sign up to set email alerts
|

Impacts des exploitations piscicoles en cages flottantes sur la structure des macroinvertébrés benthiques de la lagune Ebrié (Côte d’Ivoire)

Abstract: Les études concernant les interactions entre l'aquaculture et l'environnement sont importantes pour une gestion durable et responsable des activités aquacoles et de leurs effets environnementaux. L'appréciation des perturbations occasionnées par l'exploitation piscicole des cages flottantes installées dans la lagune d'Aghien (Secteur 1 de la lagune Ebrié) sur la communauté de macroinvertébrés benthiques sous-jacente est basée sur la comparaison des données obtenues au niveau de ces cages et celles d'une statio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
0
3
0
2
Order By: Relevance
“…Pollution indicators were revealed in this session of the basin by Capo-Chichi et al (2018) who had noticed an abun-dance of macroinvertebrates associated with organic-rich environments. Yoboue et al (2018) also reported that cage aquaculture is a source of organic pollution. Therefore, the development of cage aquaculture on Toho and Todougba lagoons explains the high degree of vulnerability observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollution indicators were revealed in this session of the basin by Capo-Chichi et al (2018) who had noticed an abun-dance of macroinvertebrates associated with organic-rich environments. Yoboue et al (2018) also reported that cage aquaculture is a source of organic pollution. Therefore, the development of cage aquaculture on Toho and Todougba lagoons explains the high degree of vulnerability observed.…”
Section: Discussionmentioning
confidence: 99%
“…These activities are likely to create modifications in the functioning of the basin in this case of the aquatic ecosystems which are the final receptacles of the whole drainage network. These modifications can lead to losses of biodiversity, fragmentation of biological habitats (Benayas et al, 2009;Dauda et al, 2014;Yoboue et al, 2018), of pollution (Degefu et al, 2011;Djihouessi et al, 2019) and other impacts that affect the biocenosis. These susceptibilities may be exacerbated by the extent of greenhouse gas production in wetlands (Deemer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…En ce qui concerne la promotion de l'aquaculture, les actions menées doivent porter sur plusieurs axes à savoir : l'encouragement des populations à l'activité par des campagnes de sensibilisation ; l'amélioration de la production des écloseries et des fermes aquacoles par la maîtrise de l'élevage larvaire et de la gestion technicoéconomique ; et la vulgarisation des techniques d'élevage de poissons en cage, avec l'appui des partenaires (Yoboue et al, 2018). Par ailleurs, l'octroi des licences est un axe primordial pour l'évolution de ce secteur.…”
Section: Opportunités Et Recommandationsunclassified
“…Le ramassage de L. varicus concerne aussi bien les adultes que les enfants contrairement à ce qui a été rapporté pour les achatines où la cueillette est principalement effectuée par les enfants (Sodjinou et al, 2001). Les perturbations anthropiques conduisent à la prolifération de la faune secondaire dont les mollusques (Abbou et Fahde, 2017 ;Yoboue et al, 2018 ;Allouko et al, 2021) qui sont majoritairement des hôtes intermédiaires dans la transmission de parasites (Opeyemi, 2009;Gbocho et al, 2015 ;Pinaud, 2017 ;Sanou et al, 2019). Ainsi, l'abondance de L. varicus dans la BVO serait liée à la perturbation anthropique de ce milieu.…”
Section: Abondance Et Importance Socioéconomique De Lanistes Varicusunclassified